Avaliação sensorial e influência do tratamento térmico no teor de ácido ascórbico de sorvete de pimenta - Dutra, Flávia Leontina Andrade; Branco, Ivanise Guilherme [UNESP]; Madrona, Grasiele Scaramal; Haminiuk, Charles Windson (Universidade Tecnologica Federal do Parana (UTFPR), 2010)
In this work were prepared with three ice cream added peppers of different varieties: Capsicum baccatum, Capsicum annuum and Capsicum frutescens. The peppers were first pasteurized and evaluated in relation to the effect of heat treatment on the ascorbic acid content. Results showed that the Capsicum annuum showed higher ascorbic acid content, but the heat treatment resulted in greater loss of biocompounds. The higher retention of ascorbic acid was observed with Capsicum frutescens, which presented lower content of biocompound, but near of the pepper Capsicum annuum. The follow attributes was performed to evaluate the acceptance of ice cream through the sensory attributes: color, aroma, flavor and texture. Analysis of variance showed no significant difference between ice cream formulations at the 5% level of significance with regard to color, aroma and texture. Regarding taste, the samples differed significantly, at 5% significance, and the most preferred was the ice cream made with pepper Capsicum frutescens.

Neste trabalho foram elaborados três sorvetes adicionados com pimentas de diferentes variedades: dedo-de-moça (Capsicum baccatum), japaleño (Capsicum annuum) e malagueta (Capsicum frutescens). As pimentas foram previamente pasteurizadas e avaliadas em relação ao efeito do tratamento térmico sobre o teor de ácido ascórbico. Resultados mostraram que a pimenta jalapeño apresentou maior teor de ácido ascórbico, porém o tratamento térmico acarretou na maior perda do biocomposto. A maior manutenção do ácido ascórbico foi verificada com a pimenta malagueta, que apresentou teor do biocomposto inferior, porém próximo à pimenta jalapeño. Foi realizada a avaliação da aceitação dos sorvetes através dos atributos sensoriais de cor, aroma, sabor e textura. A análise da variância mostrou que não existe diferença significativa entre as formulações de sorvetes, ao nível de 5% de significância, em relação à cor, aroma e textura. Em relação ao sabor, as amostras diferiram entre si, ao nível de 5 % de significância, sendo a de maior preferência o sorvete elaborado com pimenta malagueta habanero.
Sensory evaluation and the influence of heat treatment on the ascorbic acid content of pepper ice cream
Keywords: Pepper; Ice-cream; Ascorbic acid; Heat treatment; Pimenta; Sorvete; Ácido ascórbico; Tratamento térmico